Pengaruh Pengungkapan Corporate Social Responsibility (CSR) Terhadap Profitabilitas dan Manajemen Laba (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2015-2017): Keywords: Corporate Social Responsibility; Profitability; Earnings Management. - Imroatus Solikhah (Universitas Negeri Surabaya, 2022)
This study aims to examine the effect of CSR disclosure on profitability and earnings management. Purposive sampling is the method chosen in determining the sample in this study, so there are 66 samples of manufacturing companies which listed on the Indonesia Stock Exchange during the 2015-2017 period. Documentation and analysis are data collection techniques used in this study. The data analysis techniques used in this study is multiple liniear regression analysis using SPSS version 26. The results of the first dependent variable study indicate that CSR disclosure affects company profitability. While the results of the second dependent variable research indicate that CSR disclosure does not affect earnings management.